The Effects of Trunk Muscle and Cawthorne Cooksey Exercises on Reducing Fall Risk Among Older Adults - Jehaman, Isidorus; Tantangan, Redi; Sinuhaji, Simson; Nasution, Rabiatun; Ginting, Raynald Ignasius (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: Falls are a common health challenge experienced by the elderly and can significantly affect their quality of life. The leading causes of falls include decreased trunk muscle strength and disturbances in the vestibular system. Ironically, many older adults are unaware that these risks can be reduced through simple and regular physical activity. Therefore, interventions in the form of education and structured exercise, delivered directly at the community level, are considered a strategic approach to promote preventive behavior. Objective: This Community Partnership Program (PKM) aimed to  improve the knowledge, practical skills, and motivation of elderly individuals in preventing fall risks through trunk muscle exercises and Cawthorne-Cooksey exercises. Method: The activity was conducted at Pagar Jati Public Health Center, Lubuk Pakam, involving 20 elderly participants. It consisted of two main sessions: an educational session covering the causes of falls, the role of trunk muscles, and the body's balance system; and a practical session where participants performed both exercises under the guidance of the implementation team. Evaluation was carried out through initial discussions, observation of participant engagement, and a simple pre-test and post-test. Results: The program showed a significant impact. A total of 85% of participants demonstrated improved understanding of fall risk and its prevention, 78% were able to perform the exercises correctly, and 90% expressed a commitment to continue the exercises independently at home. Participant satisfaction reached 92%. The elderly showed high enthusiasm throughout the activity, with many stating that this was the first time they realized the importance of light exercises in maintaining balance. Conclusion: This activity successfully enhanced the cognitive and motor skills of elderly participants in fall prevention. The combination of trunk muscle exercises and Cawthorne-Cooksey exercises proved effective in improving postural control, vestibular adaptation, and overall body stability. This hands-on approach is highly effective and recommended for sustainable implementation within community-based health promotion and prevention programs for the elderly.